An enzymatic defect in osmotic mutants of Neurospora crassa: lack of induction of NAD(P)ase activity during growth on casein. - J. A. Jorge; A. K. Cruz; H. F. Terenzi (Fungal Genetics Reports, 1989)
An enzymatic defect in osmotic mutants of Neurospora crassa: lack of induction of NAD(P)ase activity during growth on casein.